Features of right lobe liver transplantation from living related donor - Kotenko, O. H.; Minich, A. A. (Zaporozhye Medical Journal, 2019)
Aim. To determine the peculiarities of liver transplantation using right lobe graft from living related donor with and without the middle hepatic vein inclusion. Materials and methods. The study has analyzed preoperative, intraoperative and postoperative data of 76 recipients who underwent right lobe living donor liver transplantation with different types of hepatic vein reconstruction: group 1 – patients who received a right lobe liver graft with a middle hepatic vein, and group 2 – recipients of right lobe liver graft without the middle hepatic vein. For comparative analysis, we used biochemical and regional hemodynamic parameters in both groups during the first week and on days 10, 14, 21 and 30 after transplantation. Results. In group 1, the higher values of Qpv – 649 ± 220 ml/min, 1222 ± 491 ml/min; 1264 ± 372 ml/min; 1166 ± 284 ml/min; 1016 ± 211 ml/min; 1095 ± 301 ml/min were observed compared to group 2 – 643 ± 230 ml/min; 1127 ± 385 ml/min; 1132 ± 372 ml/min; 1030 ± 263 ml/min; 980 ± 254 ml/min; 922 ± 293 ml/min on days 0, 1, 3, 5, 7 and 30 after transplantation, respectively, (P < 0.05). Peak systolic velocity (PSV) and resistance index of hepatic artery (RIha) were increased to higher values in group 2 (from 0.54 m/s to 0.69 m/s and from 0.63 to 0.69, respectively, P < 0.05) compared to group 1 (from 0.58 m/s up to0.62 m / s and from 0.62 to 0.69, respectively, P < 0.05). In the postoperative period, the level of total bilirubin in group 1 (grafts with middle hepatic vein) was significantly lower and the level of transaminases was higher than in group2. In the group of recipients, who had a graft with middle hepatic vein, the frequency of small-for-size syndrome (SFSS) was lower compared with group 2 (17.94 % vs 27.00 %, P < 0.05). Conclusions. When performing the right lobe liver transplantation, the middle hepatic vein presence in the graft is correlated with a decrease in the frequency of postoperative complications and small for size syndrome development. Adequate venous outflow with sufficient volume of right lobe liver graft determines the functional graft mass.